Expected and actual adverse drug-drug interactions in elderly patients accessing the emergency department: data from the ANCESTRAL-ED study. (1st December 2016) - Marino, A.; Capogrosso-Sansone, A.; Tuccori, M.; Bini, G.; Calsolaro, V.; Mantarro, S.; Convertino, I.; Pasqualetti, G.; Orsitto, E.; Santini, M.; Monzani, F.; Blandizzi, C.; et al.
ABSTRACT: Objective : This study was aimed at evaluating the frequency and describing the adverse drug-drug interactions (DDIs) recorded among elderly patients accessing the emergency department (ED). Methods : Patients aged ≥65 years, accessing the ED of Pisa University Hospital (Italy) from 1 January 2015 to 31 December 2015 within the ANCESTRAL-ED program, were included in this study. 'Expected' DDIs were assessed using Thomson Micromedex®. Each ED admission (discharge diagnosis) consistent with the signs and symptoms of an expected DDI for each patient was classified as an 'actual' DDI. Results : Throughout the study period, 3473 patients (3812 ED admissions, 58% females, mean age: 80.3) were recorded. The total number of expected DDIs was 12, 578 (67 contraindicated; 3334 major; 8878 moderate; 299 minor) detected in 2147 (62%) patients. Overall 464 expected DDIs were found to be consistent with the ED admission in 194 patients (representing 9% of patients with expected DDIs). Conclusions : More than one half of elderly patients admitted to ED presented at least one expected DDI at the time of ED presentation. However, 9% of the expected DDIs were identified as actual DDIs, based on the consistency of the expected event with the ED discharge diagnosis.